ROLE OF THE ADHESION MOLECULE ICAM-1 IN ASTHMA - (:unkn) unknown (MARCEL DEKKER INC, 1995)
Cells need to interact with one another for the inflammatory response to occur. The intercellular adhesion molecule-1 (ICAM-1), a member of the immunoglobulin supergene family, plays an important role in inflammation, and circulating ICAM-1 has been reported to be elevated in patients with some inflammatory disorders. To study the influence of asthma on circulating ICAM-1 levels, we measured concentrations of circulating ICAM-1 in patients with asthma. Fifteen patients (6 male, 9 female, mean age: 30 +/- 7 years) and 5 controls (2 male, 3 female, mean age: 25 +/- 6 years) were included in the study. Daily peak flow rates and symptom scores were monitored over a week in all patients and methacholine challenge tests were performed in 7 patients. The spirometric analysis of asthmatic patients demonstrated mean FEV(1): 2.57 +/- 0.97 L (74.9 +/- 17.7% predicted), mean FEV(1)/FVC: 70.1 +/- 9.6%, mean bronchodilator response: 19.2 +/- 8.4%. The mean morning peak flow rate was 331.0 +/- 122.2 L/min, the mean evening peak flow rate 389.0 +/- 118.5 L/min, the mean peripheral eosinophil count 268 +/- 451/mm(3), and the mean serum IgE level 327.4 +/- 238.2 IU/ml. The mean serum ICAM-1 levels of asthmatic patients and controls were 429 +/- 133 ng/ml and 405.0 +/- 81.0 ng/ml, respectively. There was no statistical difference between these levels. Furthermore, we could find no correlation between serum ICAM-1 levels and FEV(1), serum IgE levels, peak flowrates, and symptom scores, or methacholine PD20 values in asthmatic patients. The results of this study suggest that serum ICAM-1 levels are not increased in asthmatic patients over controls and do not correlate with clinical asthma status.